(untitled) (The Research of Medical Science Review, 2024)
Nurse’s turnover is a major problem to all health care organizations because of its strong effects on client health outcomes, motivating to work and provision of quality patient care. This study explores the push and pulls factors contributing to nurse turnover and the resulting impact on healthcare delivery. To identifies the factors contributing to nurse’s turnover. To assess the impact on patient care outcomes including quality of care and patient satisfaction. A quantitative, descriptive research design was adopted. Data was collected from 263 nurses in three hospitals using a validate questionnaire. Statistical analysis was performed using SPSS version 26. Nurse turnover adversely impacts health care delivery, resulting in delays in patient care, and patient health outcomes.